2020
DOI: 10.1021/acsami.0c10155
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Regulation of a Surface Protophilic Environment to Enhance Oxygen Reduction Reaction Electrocatalytic Activity

Abstract: Pyrolytic transition metal nitrogen–carbon (M–N/C) materials are considered as the most promising alternatives for platinum-based catalysts toward oxygen reduction reaction (ORR). As the proton-coupled electron transfer step in ORR has been proven to be a rate-determining step in the M–N/C catalysts, we envisaged that building a protophilic surface might be helpful to enhance the ORR activity. Herein, a polyaniline decoration strategy was put forward and realized to confer the Fe–N/C catalyst with a surface pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Notably, the introduction of B in Fe–N–C led to a larger C dl compared to that in Fe–N–C (10.30 mF cm –2 ), which indicated that B doped in the carbon matrix can introduce more active sites for ORR. We further calculated the TOF values for each Fe site on Fe–B–N–C and Fe–N–C to elucidate the effect of the B dopant. , The TOFs of Fe–B–N–C and Fe–N–C are 4.63 and 2.96 e·s –1 ·sites –1 , respectively, proving that B doping can improve the turnover frequency of Fe sites. In addition, KSCN was used to poison Fe sites to explore the role of Fe species in ORR. , As shown in Figure S11, when 10 mM KSCN was added to the electrolyte, the half-wave potential of Fe–B–N–C decreased by 40 mV and the limiting current density decreased by 0.463 mA cm –2 , proving that Fe sites played an important role in the catalytic process.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Notably, the introduction of B in Fe–N–C led to a larger C dl compared to that in Fe–N–C (10.30 mF cm –2 ), which indicated that B doped in the carbon matrix can introduce more active sites for ORR. We further calculated the TOF values for each Fe site on Fe–B–N–C and Fe–N–C to elucidate the effect of the B dopant. , The TOFs of Fe–B–N–C and Fe–N–C are 4.63 and 2.96 e·s –1 ·sites –1 , respectively, proving that B doping can improve the turnover frequency of Fe sites. In addition, KSCN was used to poison Fe sites to explore the role of Fe species in ORR. , As shown in Figure S11, when 10 mM KSCN was added to the electrolyte, the half-wave potential of Fe–B–N–C decreased by 40 mV and the limiting current density decreased by 0.463 mA cm –2 , proving that Fe sites played an important role in the catalytic process.…”
Section: Resultsmentioning
confidence: 94%
“…Notably, the introduction of B in Fe−N−C led to a larger C dl compared to that in Fe−N−C (10.30 mF cm −2 ), which indicated that B doped in the carbon matrix can introduce more active sites for ORR. We further calculated the TOF values for each Fe site on Fe−B−N−C and Fe−N−C to elucidate the effect of the B dopant 65,66. The TOFs of Fe−B− N−C and Fe−N−C are 4.63 and 2.96 e•s −1 •sites −1 , respectively, proving that B doping can improve the turnover frequency of Fe sites.…”
mentioning
confidence: 97%
“…The transmission electron microscope (TEM) images of carbon black and C@NC are shown in Figure a,b where the nitrogen-doped carbon shell is difficult to distinguish due to the similar contrast between the nitrogen-doped carbon shell prepared by pyrolysis of PANI and the catalyst carbon matrix . However, by comparing the carbon blacks before and after coating, we noticed a slight increase in particle size, which corresponds to the carbon support surface being covered by a carbon–nitrogen shell.…”
Section: Resultsmentioning
confidence: 96%
“…Fe-N-C catalysts have the highest ORR activity among M-N-C (M = transition metal) [ 75 , 76 , 77 ]. However, there are few reports on the direct pyrolysis of Fe-MOF materials for oxygen redox reaction.…”
Section: Mof-derived Non-precious Metal Catalystsmentioning
confidence: 99%